Produktivitas Karkas dan Daging dengan Teknik Penanganan Karkas yang Berbeda di Beberapa RPH - Rizal, A.; Nuraini, H.; Priyanto, R.; Muladno, Muladno (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2014)
Both handling and slaughtering of cattle in government and private abattoirs are varied technically. The aim of this study was to describe and to analyze variation of both handling and slaughtering techniques of cattle in abattoirs, and their effects to the meat yielded. A total of 72 local-cross cattle which is collected from 7 slaughterhouses in three provinces of Indonesia were used. Data of handling and slaughtering techniques wasdescribed, whereas carcass weight, carcass percentage, and non-carcass percentage were analyzed using T test. The results proved various processes of slaughtering processes including knocking-down of the cattle, dressing (skinning and gutting), cutting of oxtail, evisceration, carcass splitting, and trimming of subcutaneous fat were observed in this study. Approximately 63.64% of knocking-down of the cattle was supported by restraining box and stunning, 57.14% of skinning activity was done by hanging up the carcass, and evisceration process wasalso done by hanging up the carcass (85.71%). Tail docking, carcass parts, and trimming of subcutaneous fat are related to the carcass and non-carcass production. By comparing our data and SNI No.3932:2008, carcass productivity and carcass percentage were not significant statistically, however, the differences were observed quantitatively. Furthermore, tail percentage was found to be significantly different with SNI No.3932:2008 (P<0.05). In addition, our simulation discovered excess of meat production in the A, C, and D abattoirs, on theother hand, estimations of meat production in E, F, G abattoirs were deficit compared to SNI No.3932:2008. In conclusion, the larger scale of slaughterhouse could increase the estimation of meat production differences.